Total synthesis and structural revision of stagonolide D - Vadhadiya, Paresh M.; Puranik, Vedavati G.; Ramana, Chepuri V. (Journal of Organic Chemistry, 2012)
The total synthesis of the putative structure of stagonolide D has been completed. The relative and absolute configuration of stagonolide D was established by synthesizing its optical antipode. The adopted strategy involves the construction of the central macrolide employing ring-closing metathesis (RCM), followed by selective protecting group manipulations and a final concomitant −OTBS deprotection and displacement of an −OMs placed next to it, resulting in the formation of the epoxide ring.